Predicting Suffocation and Fire Risks Using IoT Systems and Machine Learning Techniques - Nobosse, Leonel Fokouong; Can, Zuhal (Fırat Üniversitesi, 2025)
This study aims to predict suffocation and fire risks using machine learning (ML) and Internet of Things (IoT) technologies. Suffocation and fire incidents are serious dangers that lead to loss of life and property. While traditional methods may be insufficient in predicting these risks, high-accuracy predictions can be achieved by using ML models and analyzing large data sets obtained with IoT-based sensor data. In this study, a comparative study of ML methods was conducted on data obtained from IoT sensors. The correlation between carbon monoxide (CO), smoke, and liquid petroleum gas (LPG) was used to predict the risk of suffocation, and the correlation between humidity, temperature, and smoke was used to predict the risk of fire. After the pre-processing steps were completed, the data were trained with models developed with linear regression, decision trees, and random forest algorithms. Experimental results show that the decision tree outperformed other algorithms by 99.99%. It was determined that the developed model worked with high accuracy rates and could play an important role in the development of risk management strategies.

Bu çalışmada, makine öğrenmesi (ML) ve Nesnelerin İnterneti (IoT) teknolojilerini kullanarak boğulma ve yangın risklerinin tahmin edilmesi amaçlanmaktadır. Boğulma ve yangın olayları, ciddi, can ve mal kayıplarına yol açan tehlikelerdir. Geleneksel yöntemler bu risklerin tahmin edilmesinde yetersiz kalabilirken, ML modelleri kullanarak ve IoT tabanlı sensör verileriyle elde edilen büyük veri kümelerinin analiziyle yüksek doğrulukta tahminler sağlanabilmektedir. Bu çalışmada, IoT sensörlerinden elde edilen veriler üzerinde ML yöntemlerinin karşılaştırmalı bir incelemesi yapılmıştır. Boğulma riskini tahmin etmek için karbon monoksit (CO), duman ve sıvı petrol gazı (LPG) arasındaki korelasyon, yangın riskini tahmin etmek için ise nem, sıcaklık ve duman arasındaki korelasyon kullanılmıştır. Veriler, ön işleme adımları tamamlandıktan sonra, doğrusal regresyon, karar ağaçları ve rastgele orman algoritmalarıyla geliştirilen modellerle eğitilmiştir. Deneysel sonuçlar, karar ağacının %99,99 doğrulukla diğer algoritmaları geride bıraktığını göstermektedir. Geliştirilen modelin yüksek doğruluk oranı ile çalıştığı ve risk yönetimi stratejilerinin geliştirilmesinde önemli bir rol oynayabileceği belirlenmiştir.
IoT Sistemleri ve Makine Öğrenmesi Teknikleri Kullanılarak Boğulma ve Yangın Risklerinin Tahmini
Keywords: Classification Algorithms; Sınıflandırma algoritmaları